The psychoactive substance use in eating disorders: a review - Pirim, Bengi; Tunaboylu İkiz, Tevfika (Journal of Dependence, 2004)
The group of psychiatric disorders subsumed under the title “eating disorders” can have fatal outcomes. Eating disorders have received increased attention as of late, but while the number of studies in this area has been growing, the etiology of this subject has yet to receive clear definition. In addiction, information regarding the relationship between eating disorders and alcohol and other substance abuse is also limited. In this article the literature of eating disorders and also alcohol and substance abuse has been reviewed. The literature on anorexia nervosa and bulimia nervosa and the relationship between these two disorders and alcohol and substance abuse has been reviewed. It was observed that in the studies reviewed, substance use and the addiction of those suffering from eating disorders had been the subject of research although the differences between the terms “substance addiction” and “substance use” had not received due consideration.